A Book Review of MOOCs Design, Application and Business Models - Mohammad Ali Rostaminezhad (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Massive Open Online Courses (MOOCs) are one of the newest phenomena in the area of integrating technology in education. The book “MOOCs Design, Use and Business Models”, which has been translated into Persian, is a university resource for scholars interested in research in this field. This 156-page book is about introducing MOOCs, design models, usage, and business models. In line with critical reviewing, in addition to using the framework introduced in the “Human Sciences Book Review Questionnaire”, evaluation criteria for academic books have also been used. In the first step, using a descriptive-analytical method, the history of MOOCs and research in this field was evaluated to achieve a book’s comparison and evaluation scale. Then, using the evaluation research method, the book was evaluated and criticized. Using content-related criteria, methodology, lingual, structural, appearance, and front and back matter indicators, the book was evaluated at a moderate level. From the instructional perspective, the work was introduced as a supplementary source. The strength of the book is its applicability and relevance, and its weakness was the lack of consistency of content and the mismatch of content with the title and poverty of theoretical foundations. Fluent translation and the correspondence with the main content was one of the most important strengths of the translation, and the need for explanations of the translator in the footnotes and the complete presentation of the abbreviations were the weaknesses of the translation. These findings were discussed, and suggestions were presented.